2012
DOI: 10.1103/physrevlett.109.105702
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Maximum Velocities in Avalanches Near the Depinning Transition

Abstract: We report exact predictions for universal scaling exponents and scaling functions associated with the distribution of the maximum collective avalanche propagation velocities v(m) in the mean field theory of the interface depinning transition. We derive the extreme value distribution P(v(m)|T) for the maximum velocities in avalanches of fixed duration T and verify the results by numerical simulation near the critical point. We find that the tail of the distribution of maximum velocity for an arbitrary avalanche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
3
15
1
Order By: Relevance
“…10. This behavior is consistent with recent predictions in mean field theory (LeBlanc et al, 2012). In particular, such theory also derived a value of scaling exponent $2 for those larger velocities.…”
Section: Burst Velocitysupporting
confidence: 87%
See 1 more Smart Citation
“…10. This behavior is consistent with recent predictions in mean field theory (LeBlanc et al, 2012). In particular, such theory also derived a value of scaling exponent $2 for those larger velocities.…”
Section: Burst Velocitysupporting
confidence: 87%
“…7b, the calculated burst time durations show statistics consistent with the experimental data (Papanikolaou et al, 2012a). Despite the good agreement of the calculations from the present model with the predictions in mean-field theory (LeBlanc et al, 2012), it is still an open problem as to what extent it can describe the pillar size with the diameters smaller than $10 lm. For example, recent reports of compression tests of Au nano-and microcrystals have also shown that the distribution of burst velocity follows a power law behavior (Maaß et al, 2013), but the values of the scaling exponent are different from the present results.…”
Section: Burst Velocitysupporting
confidence: 77%
“…The main results for fixed durations at the critical point have been recently reported in Ref. [29]. Here, we present the details of the calculations and extend the work to also include the effects of nonzero sweep-rate c and the maximum velocity statistics for fixed avalanche size.…”
Section: Quantitiymentioning
confidence: 72%
“…We have already seen in Ref. [29] that the driving rate dependence of the power law P (v m ) ∼ v −µ m at criticality is µ = 2 −c. In Fig.…”
Section: Overall Duration Size and Maximum Velocity Distributionsmentioning
confidence: 99%
See 1 more Smart Citation